“Political Liberalism” By John Rawls- A Review - Dr Ayesha sabeen (International Research Journal of Arabic and Islamic Studies, 2024)
This article is a review of an important book “Political Liberalism” by John Rawls. He is a famous philosopher of 20th century. This book is a modified edition of Rawls previous book “A Theory of Justice”. The aim of political Liberalism is to achieve a political notion that religious and non-religious, liberal and non-liberal may live freely.